2020
DOI: 10.1002/ps.5978
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic toxicity of deltamethrin, permethrin, and dihaloacetylated heterocyclic pyrethroids in mice

Abstract: BACKGROUND: Pyrethroids, a class of insecticides, that act on the nervous system of insects. Frequent consumption of foods with pyrethroid residues increase the risk of developmental and neurological diseases in humans. Assessing the toxicity of novel synthetic pyrethroids to mammals is also critical to the development of agrochemicals. RESULTS: Using mice as models, the acute and chronic toxicity of deltamethrin, permethrin, dihaloacetylated pyrethroids to mammals was researched by gavage administration. Acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The biological effects of their exposure at low concentration can be attributed to severe pathologies in animal and human health. [43] Our results showed that permethrin exposure caused a significant reduction of body weight [44] with an increase of absolute and relative liver weights. The reduction in the body weight could presumably be ascribed either to the decrease of food intake and/or malabsorption of nutrients in rats and also to the action of PER on the gastrointestinal tract and/or inhibition of protein synthesis.…”
Section: Discussionmentioning
confidence: 60%
“…The biological effects of their exposure at low concentration can be attributed to severe pathologies in animal and human health. [43] Our results showed that permethrin exposure caused a significant reduction of body weight [44] with an increase of absolute and relative liver weights. The reduction in the body weight could presumably be ascribed either to the decrease of food intake and/or malabsorption of nutrients in rats and also to the action of PER on the gastrointestinal tract and/or inhibition of protein synthesis.…”
Section: Discussionmentioning
confidence: 60%
“…The acute oral toxicity test was conducted according to the established methods. 22,24,28,29 In this experiment, ten female and ten male healthy-looking mice were selected and divided randomly into two experimental groups. Each group consisted of five males and five females.…”
Section: Acute Toxicity Testmentioning
confidence: 99%
“…Additionally, assessment of the potential risk of chemical substances to mammals is crucial for the development of agrochemicals. 21,22 There is a considerable interest in the safety assessment of the metabolites of ME. Therefore, in the current study, we first evaluated the actual behavioral attractiveness of E-CF and DMP for mature females.…”
Section: Introductionmentioning
confidence: 99%
“…Some investigations have been carried out on the high-dose short-term toxicity of permethrin [ 15 , 16 ]. In reality, however, the actual exposure to the insecticide is usually at low-level and for long-term [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%